Effect of monoamine oxidase B A644G variant on nicotine dependence and/or schizophrenia risk (Archives of Clinical Psychiatry, 2019)
Objectives: Schizophrenia (Sch) is a severe and chronic mental illness. Smoking prevalence is higher in patients with Sch than general population. We aimed to investigate the effects of MAOB gene A644G variant on nicotine dependence (ND) and Sch+ND risk in Turkish population and to evaluate by bioinformatic analysis. Methods: Present study included 161 individuals with ND, 223 patients with Sch+ND, and 96 non-smoker controls. MAOB A644G variant was analyzed using PCR-RFLP method. As the MAOB gene is located on the X chromosome, each gender was analysed separately. Results: The total distributions of AA, AG and GG genotypes of MAOB gene A644G were 44.7%, 22.4% and 32.9% in the ND group, 45.3%, 25.1% and 29.6% in the Sch+ND group and, 44.8, 22.9% and 32.3% in non-smoker controls. No significant differences were observed between groups for the MAOB A644G genotype and allele frequencies when female group compared to male group (p > 0.05). Examination of disease associations of SNPs from each miRNA gene region in GWAS databases yielded results for aging, bipolar disorder, autoimmune, and neurological diseases. Discussion: Our results indicate that the MAOB gene A644G variant is not associated with ND and/or Sch susceptibility in the Turkish population.